Utilization of used components : in new electrical and electronic products in accordance with IEC 62309 - Belli, Fevzi; Quella, Ferdinand (VDE Verlag GMBH, 2015)
Saving our environmental resources is a challenge and can only be achieved in the future through the reuse of components in new products. About 25 % of the existing electrical and electronic (E & E) components are suitable for reuse. In Europe, reuse is considered to be the best waste handling procedure. Therefore, reuse happens to be favored politically by a number of authorities at various levels, both national and European, which will increase its importance and relevance for industrial production. The present European Waste Framework Directive confirms this view. As a result, many non-European countries already have, or are preparing, similar directives. This will certainly lead to an increase in pressure to reuse components, supported by forthcoming international normative references, including legal and industrial standardization.
Keywords: Electronics -- Materials.; Salvage (Waste, etc.); Recycled products.; elektronické knihy; electronic books